The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1152/ajprenal.00261.2010
|View full text |Cite
|
Sign up to set email alerts
|

Temporal characterization of the development of renal injury in FHH rats and FHH.1BNcongenic strains

Abstract: The present study examined the effect of transfer of portions of chromosome 1 that includes (FHH.1(BN) AR(+) strain) or excludes (control FHH.1(BN) AR(-) strain) a 4.3-Mb region from the Brown Norway (BN) rat that restores the autoregulation (AR) of renal blood flow (RBF) on the development of hypertension and renal injury in congenic strains of Fawn Hooded Hypertensive (FHH) rats. FHH and control AR(-) rats exhibited poor autoregulation of RBF, and glomerular capillary pressure (Pgc) rose by 19 ± 2 mmHg in FH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 37 publications
0
38
0
Order By: Relevance
“…Thus, in the congenic FHH.1 BN AR þ strain autoregulation of renal blood flow was normalized and a decrease in the progression of renal disease was observed (Table 2). 91,103 It was suggested that before hypertension occurred an impaired autoregulation in FHH may lead to early onset of renal disease such as glomerulosclerosis and renal interstitial fibrosis. 103 The genetic basis of albuminuria linked to the Rf-2 on RNO1 was elucidated by identifying Rab38 (RAB38, member RAS oncogene family) as a potential candidate gene within this locus.…”
Section: Loc501853mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in the congenic FHH.1 BN AR þ strain autoregulation of renal blood flow was normalized and a decrease in the progression of renal disease was observed (Table 2). 91,103 It was suggested that before hypertension occurred an impaired autoregulation in FHH may lead to early onset of renal disease such as glomerulosclerosis and renal interstitial fibrosis. 103 The genetic basis of albuminuria linked to the Rf-2 on RNO1 was elucidated by identifying Rab38 (RAB38, member RAS oncogene family) as a potential candidate gene within this locus.…”
Section: Loc501853mentioning
confidence: 99%
“…91,103 It was suggested that before hypertension occurred an impaired autoregulation in FHH may lead to early onset of renal disease such as glomerulosclerosis and renal interstitial fibrosis. 103 The genetic basis of albuminuria linked to the Rf-2 on RNO1 was elucidated by identifying Rab38 (RAB38, member RAS oncogene family) as a potential candidate gene within this locus. 104 An Table 4.1 Distribution of QTL associated with renal (disease) phenotypes in the rat genome.…”
Section: Loc501853mentioning
confidence: 99%
“…1, restored autoregulation (48). The goal of the present study was to create additional double subcongenic strains to narrow the region of interest further so that positional candidate genes could be prioritized by sequencing and expression studies.…”
Section: Protocol 1: Generation Of Subcongenic Strains From Fhh1bn Cmentioning
confidence: 99%
“…kidney; glomerulosclerosis; chronic renal failure; renal hemodynamics THE FAWN-HOODED HYPERTENSIVE (FHH) rat is a genetic model of hypertension (33) that develops proteinuria, glomerulosclerosis (21,30,37,47), and chronic kidney disease (22,(25)(26)(41)(42). We have previously reported that the development of proteinuria and glomerular injury in FHH rats is associated with an impaired autoregulation of renal blood flow (RBF), glomerular filtration rate (GFR), and glomerular capillary pressure (Pgc) (24,40,43,48). Genetic cosegregation studies identified five quantitative trait loci (QTLs) linked to the development of proteinuria in F2 crosses of FHH and AugustCopenhagen inbred (ACI) rats (4 -5, 36).…”
mentioning
confidence: 99%
See 1 more Smart Citation